1232 Lung cancer and occupational social status: the synergy study. (24th April 2018) - Behrens, Thomas; Hovanec, Jan; Siemiatycki, Jack; Conway, David I; Olsson, Ann; Kromhout, Hans; Vermeulen, Roel; Straif, Kurt; Jöckel, Karl-Heinz; Brüning, Thomas
Abstract : Introduction: Several studies associated low socioeconomic status (SES) with lung cancer. However, many were not able to consider smoking behaviour appropriately. We took advantage of the international SYNERGY study of pooled case-control studies with detailed information of smoking habits and the occupational history to study the association between lung cancer and occupationally derived SES. Methods: Twelve case-control studies from Europe and Canada were included. We estimated SES based on the subjects' complete occupational histories using the International Socio-Economic Index of Occupational Status (ISEI) and the European Socio-economic Classification (ESeC). ISEI was categorised into four equidistant categories comprising the same number of codes and, secondly, according to quartiles of the sex-specific score distribution among control subjects. We calculated odds ratios (OR) and 95% confidence intervals (CI) by unconditional logistic regression, adjusting for age, study, and smoking behaviour, and stratified by sex. Subgroup analyses by lung cancer histological subtype, study region, birth cohort, education, and occupational exposure to known lung carcinogens were also carried out. Result: We included 17 021 cases and 20 885 control subjects into the final analysis. There was a strongly elevated association of lung cancer with low SES in the analysis adjusted for age and study. Adjustment for smoking attenuated the associations, however, a social gradient with lung cancer persisted. Comparing the lowest vs highest SES category in men yielded: ISEI OR=1.84 (95% CI: 1.61 to 2.09) and ESeC OR=1.53 (95% CI: 1.44 to 1.63). ORs for women were slightly lower: ISEI OR=1.54 (95% CI: 1.20 to 1.98) and ESeC OR=1.34 (95% CI: 1.19 to 1.52). Discussion: Low SES remained an independent risk factor for lung cancer even after controlling for smoking habits.